Non-Tariff Measures and other Trade Measures for the Environment in ASEAN - Jaime de Melo; Jean-Marc Solleder (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
An open world trading system with low barriers to trade in Environmental Goods (EGs) and Environmental Services (ESs) accompanied by corrective SPS and TBT measures is necessary for the World Trading System to be compatible with the environmental objectives in the SDGs. So far, the political process and technical difficulties in defining EGs and ESs have plagued multilateral negotiations under the Doha Round and those under the Environmental Goods Agreement (EGA) resulting in lists of EGs and ESs with many weaknesses.The chapter explores differences in policy measures across broad categories of EGs and ESs. Comparisons of EG and non-EG groups reveal that applied tariffs are lower for EGs for all countries and group of countries regardless of the selected EG list. On average, descriptive indices of NTMs are quite similar for EG and non-EG product lists revealing few robust differences between EGs and non-EGs and across countries. However, the regulatory distance is less among ASEAN membership than among EGA membership, suggesting more favourable prospects for fruitful negotiations in the ASEAN group. The paper closes with gravity-based panel estimates of bilateral trade. Two results stand out: on average, NTMs restrict bilateral trade by about 20 percent, but not differently for EGs than for non-EGs or for ASEAN countries as a group relative to other countries. The chapter concludes with suggestions for reduction in tariffs for suitably defined EGs and more open regulatory measures for ESs.
Keywords: 330; NTM; non tariff measures